Analisis Diversifikasi Aset, Risiko dan Ukuran BPR Terhadap Efficiency pada BPR yang terdaftar di OJK - Prince Dermawan; Poniman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the impact of asset diversification, credit risk, and the size of Rural Banks (BPR) on operational efficiency at BPRs registered with the Financial Services Authority (OJK) during the period of 2019-2022. The study shows that asset diversification does not significantly affect BPR efficiency, with a Loan to Deposit Ratio (LDR) coefficient of 0.329830 and a probability of 0.7441, indicating that poorly managed diversification can increase operational risks and decrease efficiency. Previous studies support this finding, suggesting that BPRs should select more targeted investment portfolios to reduce risks and support efficiency. On the other hand, credit risk, measured by the Non-Performing Loan (NPL) ratio, has a significant positive effect on BPR efficiency, with a coefficient of 2.300770 and a probability of 0.0294. The higher the NPL, the greater the credit risk faced, leading to increased operational costs and decreased efficiency. Meanwhile, BPR size has a significant positive impact on efficiency, with a coefficient of 2.57133 and a probability of 0.0022, indicating that larger banks tend to be more efficient due to greater access to financial resources and better economies of scale. Overall, asset diversification, credit risk, and BPR size together explain 87.5% of the variation in BPR efficiency. Therefore, BPR management needs to focus on good risk management and maintain a balance between asset diversification and bank size to sustainably improve operational efficiency.